Diversity-focused HR practices and perceived firm performance: mediating role of procedural justice. Issue 2 (21st March 2019) - Kundu, Subhash C.; Mor, Archana; Bansal, Jahanvi; Kumar, Sandeep
Abstract : Purpose: The purpose of this paper is to investigate the relationship between diversity management (i.e. diversity-focused human resource (HR) practices related to recruitment and selection, training and development, performance appraisal and compensation) and perceived firm performance, and the mediating effect of procedural justice. Design/methodology/approach: Primary data based on 400 respondents of 162 organizations operating in India were analysed using statistical tools such as factor analysis, analysis of variance (ANOVA) and multiple regression analysis. Findings: Multiple regression analysis indicated that diversity-focused HR practices had a positive association with perceived firm performance. Further, it was found that procedural justice played a partially mediating in the relationship between diversity-focused HR practices and perceived firm performance. Research limitations/implications: This paper relied on self-report surveys for data collection, and there laid a possibility of common method variance in the result findings. Hence, future studies should collect data from multiple sources by using multiple methods (e.g. interviews, surveys, peer reports, etc.). Practical implications: The first implication highlights that senior management's support is a prerequisite to execute justice-based diversity management processes, which in turn aid in harvesting the true potentials of diversity. Second, organizations should adopt an egalitarian approach while formulating and implementing diversity management initiatives to accentuate the fair and just perceptibility of procedures among employees. Originality/value: This study sheds new light on the effects of diversity-focused HR practices on firm performance (perceived) in Indian context.